2021
DOI: 10.1016/j.ihj.2020.11.147
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of thyroid hormone alterations in acute coronary syndrome–A systematic review

Abstract: There is considerable association of thyroid function and the cardiovascular system during various acute systemic illnesses. It is well established that the normal thyroid homeostasis is known to alter in disease states including the acute coronary syndromes (ACS). Abnormal thyroid hormonal status has been shown to be related to worse outcomes and prognosis. This review focuses on the relationship of alterations in thyroid function and its influence on the pathophysiological mechanisms and cardiovascular hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…These assume special importance in patients with ACS as reported in many studies. (Arambam et al 2021). Thyroid dysfunction is more common in female preponderance (52%), as seen in our study and this has been an observation in several other studies also.…”
Section: Discussionsupporting
confidence: 89%
“…These assume special importance in patients with ACS as reported in many studies. (Arambam et al 2021). Thyroid dysfunction is more common in female preponderance (52%), as seen in our study and this has been an observation in several other studies also.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence rate of ACS and diabetes was as high as 24%–30%, and the risk of in-hospital and long-term major adverse cardiovascular events and complications was significantly higher than that of patients without diabetes ( 5 , 6 ). Some previous retrospective studies with a small sample have found that the proportion of ACS patients with thyroid dysfunction is about 20%–30% ( 7 , 21 ). As is known to all, the rates of heart failure, nonfatal reinfarction, unplanned repeat revascularization, and all-cause or cardiac mortality are high in ACS patients with thyroid dysfunction, including hyperthyroidism, hypothyroidism, and even subclinical thyroid disease ( 7 , 8 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous retrospective studies with a small sample have found that the proportion of ACS patients with thyroid dysfunction is about 20%–30% ( 7 , 21 ). As is known to all, the rates of heart failure, nonfatal reinfarction, unplanned repeat revascularization, and all-cause or cardiac mortality are high in ACS patients with thyroid dysfunction, including hyperthyroidism, hypothyroidism, and even subclinical thyroid disease ( 7 , 8 , 22 ). However, in euthyroid patients with normal serum thyroid function indexes, it is very critical to evaluate real thyroid function, identify thyroid dysfunction, and explore its relationship with the prognosis of ACS with diabetes ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Euthyroid sick syndrome" stands out as the most prevalent condition in patients grappling with ACS. This condition is characterized by an alteration in the typical feedback regulation mechanism of thyroid homeostasis and presents with reduced levels of serum triiodothyronine (T3) and/or free triiodothyronine (fT3), elevated levels of serum reverse triiodothyronine (rT3), and concurrently normal levels of blood thyroid stimulating hormone (TSH), thyroxine (T4), and free thyroxine (fT4) [ 5 , 8 , 9 ]. Notably, this condition has been reported in many cases of severe chronic heart failure [ 10 , 11 ] and acute MI [ 12 , 13 ], and as a rapidly arising condition after open-heart surgery [ 8 ].…”
Section: Introductionmentioning
confidence: 99%